Development of Radioactive Sources on the Basis of Bioinert Ceramic Materials for Medical Applications and their Pre-Clinical Testing; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Khabas (Habas) T. A. Tamara Andreevna; Kulinich E. A. Ekaterina Aleksandrovna; Merkulov V. G. Viktor Georgievich; Roesli С.; Martusevich M. (Chemical Technologies, 2014)
Title screen